FOSTERING CRITICAL THINKING SKILLS THROUGH SOCRATIC QUESTIONING: INSIGHTS FROM WIDYATAMA UNIVERSITY - Hero Gunawan; Ervina CM Simatupang; Puspita Sari (University of Kuningan, 2024)
Abstract: This paper discusses the use of Socratic questioning method (SQM) to enhance students’ critical thinking capability. The method used in this research was descriptive – the method that describes a given state of affairs as fully and carefully as possible (Fraenkel, 1990:11). Twelve students of English Department S-1 Program sitting in the 4th semester participate in this research. This SQM is applied in learning process for the subject of Academic Presentation. Data were gathered through the two instruments, classroom observation and closed-ended questionnaires. The questionnaire consisted of ten items divided into six parts: understanding of SQM, critical thinking capabilities, application of SQM, effectiveness of SQM, perception of learning using SQM, and effects on critical thinking capability The results of the study indicate that: 1) the questions posed by the students are in level of analysis, 2) the contents of the questions posed cover identifying, relating, analyzing, and making inferences of the topics under discussion, and 3) the benefits of using SQM include provoking deep analysis, promoting critical thinking, making the one being asked think hard, maintaining learning motivation, and making students feel confident during the discussion sessions. The implementation of the Socratic Questioning Method (SQM) in the